A Cross-Case Analysis of Sophomore Students’ Reflections on Self-Efficacy: Signals for Innovative Sophomore Programming (Higher Education Politics and Economics, 2025)
The persistence of sophomores warrants more attention. We used self-efficacy theory to conceptualize how sophomore students described their mastery of course-related tasks, social engagement, and connection, or lack thereof, to the campus and university, and what influenced their confidence. In a qualitative cross-case analysis of data drawn from a sequential mixed-methods explanatory study on the self-efficacy of undergraduate sophomore students (n = 20), we found disparities between low (n = 5) versus high (n = 15) levels of self-efficacy, especially among sophomore transfer students who lived off campus. Findings indicate course-related tasks presented challenges for participants irrespective of self-efficacy scores, engagement was externally motivated, and involvement fostered connectivity and growth in self-efficacy. Implications for practice include the creation of innovative sophomore programming.